Calibration of gamma-ray detectors using Gaussian photopeak fitting in the multichannel spectra with a LabVIEW-based digital system. (17th August 2017) - Schlattauer, Leo; Parali, Levent; Pechousek, Jiri; Sabikoglu, Israfil; Celiktas, Cuneyt; Tektas, Gozde; Novak, Petr; Jancar, Ales; Prochazka, Vit
Abstract: This paper reports on the development of a gamma-ray spectroscopic system for the (i) recording and (ii) processing of spectra. The utilized data read-out unit consists of a PCI digital oscilloscope, personal computer and LabVIEW™ programming environment. A pulse-height spectra of various sources were recorded with two NaI(Tl) detectors and analyzed, demonstrating the proper usage of the detectors. A multichannel analyzer implements the Gaussian photopeak fitting. The presented method provides results which are in compliance to the ones taken from commercial spectroscopy systems. Each individual hardware or software unit can be further utilized in different spectrometric user-systems. An application of the developed system for research and teaching purposes regarding the design of digital spectrometric systems has been successfully tested at the laboratories of the Department of Experimental Physics.